The influence of generational differences on the Malaysian housing preferences / Hafiszah Ismail - Ismail, Hafiszah (Institute of Graduate Studies, UiTM, 2017)
Literatures and models on property development evidences demographics as the long term trends especially the populations as one of the main factors that influence the property development process. Changes of demographics would influence the economic in general and the property market in specific besides the public policy implications that may also affects the behaviour of many actors of the property development sector. People live in households and households need housing and thus various demographic changing trends would contribute to dramatic change that affects the society and the generations. Changing demographic trends would give effects on the property market especially on the housing demand thus this give reason why more studies especially on the relationship between population and housing is greatly needed. Previous studies on demographic changes and housing demand show that focus were given mainly to the senior (elderly) generation namely the ‘Baby Boom/Baby Boomers’ Generation especially on the impacts toward the housing prices. As the numbers of this senior (elderly) population and their mean age currently continues to increase and projected to continually arise annually alongside with the other populations due to improvement of the health quality and lifestyle thus studies on current and future senior (elderly) housing preferences were relevant to guarantee better housing provisions of this specific population. In relevance, differences between generations have a large influence on our society, with younger generations continually being accompanied by new and different attitudes and values’ (Roberts et. al., 2000). Therefore, there is also an imperative need to include different categories of generation namely Generation X (Gen-X), Generation Y (Gen-Y) and Generation Z (Gen-Z) in the discussions of housing particularly on the preferences. Despite on the importance, intense debate on how demographics drive the demand for housing reveals that empirical evidence is still not conclusive, especially in an international context…